Evolusi Pertanian Di Era Society 5.0 - Satria Yuda Setiawan; Aji Wibawa (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2022)
This research discusses the readiness of Indonesian agriculture to face the Society 5.0 era. Agriculture is an important sector that provides food for humans worldwide, including Indonesia. However, agriculture in Indonesia is facing challenges in facing the super-smart society. This study used qualitative descriptive analysis methods by collecting and evaluating quality and relevant references with certain criteria. The results showed that Indonesian agriculture needs to prepare for several aspects such as the use of new technology, improving the quality of human resources, implementing environmentally friendly farming practices, and increasing target markets to face existing challenges. If Indonesian agriculture is ready to face the Society 5.0 era properly, the agricultural sector will become more productive and sustainable in the future to support the sustainability of human life. Penelitian ini membahas mengenai kesiapan pertanian Indonesia dalam menghadapi era Society 5.0. Pertanian merupakan sektor penting yang menyediakan makanan bagi manusia di seluruh dunia, termasuk Indonesia. Namun, pertanian di Indonesia dihadapkan pada tantangan untuk menghadapi masyarakat super pintar. Penelitian ini menggunakan metode analisis deskriptif kualitatif dengan mengumpulkan dan mengevaluasi referensi berkualitas dan relevan dengan kriteria tertentu. Hasil penelitian menunjukkan bahwa pertanian Indonesia perlu mempersiapkan beberapa aspek seperti penggunaan teknologi baru, meningkatkan kualitas sumber daya manusia, mengimplementasikan praktik pertanian yang ramah lingkungan, dan meningkatkan target pasar untuk menghadapi tantangan yang ada. Jika pertanian Indonesia siap menghadapi era Society 5.0 dengan matang, maka sektor pertanian akan menjadi lebih produktif dan berkelanjutan di masa depan untuk mendukung keberlangsungan hidup umat manusia.